Upaya Membangun Kesadaran Tentang Hidrasi Anak Sekolah Full Day di Padang - Fasrini, Ulya Uti; Ilhami, Yose Ramda; Lailani, Mutia; Welan, Rahmani; Irramah, Miftah (Poltekita: Jurnal Pengabdian Masyarakat, 2024)
Adequate fluid intake is associated with students' attention, memory function, and cognitive performance. Sekolah Alam Ar Royyan, one of the schools highlighted in the G20, needs assistance with students' low water drinking behavior. The hydration team's preliminary research found that most students were mild-moderate dehydrated, which was closely related to action. This activity aims to build awareness of the school and its community to build a culture of drinking enough water at school. The method used was action research involving school administrators, students, and teachers. The researcher identifies specific problems, collects relevant data, analyzes the data, and then decides on the needed actions to overcome these problems. After implementing a series of activities, the team conducted the evaluation. The results showed that eight out of ten students were moderately dehydrated, had low water drinking habits at school, and had limited availability of clean drinking water. After conducting activities with a participatory approach, water drinking at school began to increase, although yet to be significant, and the school has provided drinking water in gallons that students can access while at school in each classroom. This activity concludes that there has been an increase in awareness from the entire school academic community about fulfilling the adequacy of students' drinking water at school.